Bibliometric Visualization of Global Trends in Financial Literacy and Digital Household Debt 2020-2025 - Maria Suryaningsih; Susi Susilawati; Ramdany; Ridwan saleh; Samukri (PT FORMOSA CENDEKIA GLOBAL, 2026)
Low levels of financial literacy are a major factor contributing to household debt and poor financial decision-making. This study aims to map the development of literature on financial literacy and household debt during 2020–2025 using a bibliometric approach. A total of 427 Scopus-indexed articles were analyzed using Bibliometrix (RStudio) and VOSviewer. The findings reveal that financial literacy is strongly associated with financial education, debt behavior, and financial resilience. The United States and Indonesia were the leading contributors, while Olivia S. Mitchell and Annamaria Lusardi emerged as influential authors in scientific collaboration networks. The study concludes that financial literacy plays a strategic role in shaping household financial behavior and reducing over-indebtedness. It recommends contextual educational programs, international research collaboration, and longitudinal studies to strengthen long-term impacts.